The multifaceted role of autophagy in skin autoimmune disorders: a guardian or culprit? - Lin, Yi; Wu, Xiuyi; Yang, Yiwen; Wu, Yue; Xiang, Leihong; Zhang, Chengfeng (Frontiers in Immunology, 2024)
Autophagy is a cellular process that functions to maintain intracellular homeostasis via the degradation and recycling of defective organelles or damaged proteins. This dynamic mechanism participates in various biological processes, such as the regulation of cellular differentiation, proliferation, survival, and the modulation of inflammation and immune responses. Recent evidence has demonstrated the involvement of polymorphisms in autophagy-related genes in various skin autoimmune diseases. In addition, autophagy, along with autophagy-related proteins, also contributes to homeostasis maintenance and immune regulation in the skin, which is associated with skin autoimmune disorders. This review aims to provide an overview of the multifaceted role of autophagy in skin autoimmune diseases and shed light on the potential of autophagy-targeting therapeutic strategies in dermatology.